Combating crises and deflation in China's central bank: Modeling post-pandemic monetary policymaking - Richard C. K. Burdekin; Pierre L. Siklos (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2025)
The monetary policy of the People's Bank of China (PBoC) during 2001-2023 is assessed in terms of Taylor and McCallum rules, as well as a proposed composite monetary policy rule. PBoC policy is found to be responsive to the gap between target and actual nominal GDP in the McCallum rule, as well as the output and inflation gaps in the Taylor rule. We find a relatively close fit between actual and predicted monetary policy moves under both rules, and a superior fit with our composite rule incorporating monetary and interest-rate factors. The policy reactions persist across a series of transitions between high- and low-volatility regimes identified via Markov-switching regressions. The results are shown to be robust using several techniques.
urn:nbn:fi-fe2025041025516
Keywords: E58; E52; 330; monetary policy; People's Bank of China; policy rules; inflation; deflation